Use of microteaching as a tool to improve teaching skills among assistant professors in Medical College - Berad, Aditya S.; C., Balakrishna (International Journal Of Community Medicine And Public Health, 2022)
Background: Microteaching is a well-recognized tool for improvement of teaching skills. It scales down the complexities of real teaching, as immediate feedback can be sought after each practice session. The aim of the study was to evaluate the application of microteaching principles for improving teaching skills of Assistant Professors in medical college. Methods: Assistant Professors were asked to prepare a topic for tutorial lesson and engage one batches of II MBBS students (session I). The students assessed the performance of the Assistant Professors and gave immediate feedback to the faculty. The feedback focused on appreciating the good points and giving tips for improvement of group facilitation skills and teaching skills. The Assistant Professors then engaged another tutorial class on different topics (session II). Results: The results of the evaluation after two microteaching sessions showed that there was significant improvement in the teaching skills of the assistant professors. Lesson on the whole was effective. Conclusions: The teaching skills of assistant professors improved after the two sessions of microteaching. The faculty had more confidence in teaching after the study. Microteaching can be used as a tool to improve teaching skills among assistant professors in medical college.